Maternal and psychosocial antecedents of anxiety and depression in extremely low gestational age newborns at age 15 years - Jalnapurkar, Isha; Oran, Ali; Frazier, Jean A.; Cochran, David; Kim, Sohye; Jensen, Elizabeth; Joseph, Robert; Hooper, Stephen R.; Santos, Hudson; Jara, Hernan; Kuban, Karl C. K.; Msall, Michael E.; et al. (Frontiers in Child and Adolescent Psychiatry, 2024)
The prevalence of many psychiatric symptoms, including anxiety and depression, is higher in individuals born extremely preterm (EP) than in term-born individuals during childhood and adolescence. In this prospective study of adolescents born EP, we examined associations between early-life risk factors (prenatal maternal health conditions, socioeconomic and social factors) and anxiety and depression at 15 years of age.We included 682 participants (53.2% White, 57.8% male) who were born <28 weeks gestation. Data on demographic factors, maternal health conditions and socioeconomic status (SES) were collected in the first postnatal month, and data on the outcomes (anxiety and depression) were collected at 15 years by a structured clinical diagnostic interview. At the 15year visit, the mother reported on her own experiences of childhood trauma. Logistic regression models were used to evaluate associations between maternal health indicators, SES factors and mothers' childhood trauma and adolescent outcome variables of anxiety, depression and both anxiety and/or depression, adjusting for potential confounding factors and expressed as adjusted odds ratios (aOR) and 95% confidence intervals (CI).Results: Maternal pre-pregnancy obesity was associated with anxiety (aOR 1.84, 95%CI 1.15, 2.95) and depression (aOR 1.95, 95%CI 1.17, 3.23) in adolescents at age 15. Maternal exposure to active or second-hand smoke was associated with depression (aOR 1.8, 95%CI 1.08, 3.00) and with anxiety and depression (aOR 2.83, 95%CI 1.51, 5.31) at age 15. Other maternal pre-pregnancy health indicators of interest including asthma, hypertension and diabetes mellitus did not demonstrate significant associations with symptoms of anxiety or depression in adolescents at age 15 in univariable and multivariate analyses. Maternal childhood experience of parental upheaval was associated with anxiety and depression (OR 1.91, 95%CI 1.01, 3.55) in adolescents, and maternal childhood experience of victim violence was linked with anxiety (OR 2.4, 95%CI 1.22, 4.62) and anxiety and depression (OR 2.49, 95%CI 1.05, 5.42).These findings suggest that prenatal maternal health and socioeconomic factors contribute to psychiatric disorders among adolescents born EP. These factors could serve as targets for interventions to improve mental health of individuals born EP.